ACADEMIC ACTION OF THE DENTISTRY COURSE IN THE CITIZEN'S ITINERANT PROJECT - MOTHER'S DAY (CIPEEX, 2022)
OBJECTIVE: THIS STUDY AIMS TO PRESENT THE EXPERIENCE REPORT OF THE CITIZEN ITINERANT PROJECT - MOTHER'S DAY WITH THE PARTICIPATION OF THE DENTISTRY COURSE OF THE UNIVERSITY CENTER OF ANÁPOLIS - UNIEVANGLICA WITH THE INTENTION OF ORIENTING ON THE FORMS OF ORAL CANCER PREVENTION, EDUCATING CHILDREN AND EMPLOYEES ON THE IMPORTANCE OF ORAL HEALTH, AND ENCOURAGE IMPROVEMENTS IN THE TECHNIQUE OF BRUSHING TO MAKE THEM A HABIT. METHODS: THE STUDENTS WERE EVALUATED BY THE ORAL CAVITY EXAMINATION, ORAL HYGIENE TECHNIQUE AND SUPERVISED BRUSHING AS ARTICULATED WITH THE DISCIPLINE OF THE PUBLIC HEALTH POLICY PROJECT OF THE DENTISTRY COURSE, AS WELL AS GUIDANCE ON PREVENTION OF ORAL CANCER AND ORAL HYGIENE. RESULTS: THE STUDENTS OF THE COURSE OF DENTISTRY WERE ABLE TO EXPERIENCE A DIFFERENT REALITY FROM WHICH THEY ARE ACCUSTOMED IN AN ACADEMIC ENVIRONMENT. HEALTH EDUCATION ACTIONS WERE CARRIED OUT WITH ORAL HYGIENE TECHNIQUE, SUPERVISED BRUSHING FOR CHILDREN, WITH A TOTAL OF 84 CHILDREN WHO HAD TO SPEND IN BOTH ACTIVITIES, AND THE ORAL CANCER PREVENTION ACTION IN WHICH 30 EXAMINATIONS WERE PERFORMED, TOTALING 114 PEOPLE AS A TARGET AUDIENCE. FINAL CONSIDERATIONS: THE COMMUNITY BENEFITED BY APPROACHING SUBJECTS IN WHICH THEY DID NOT HAVE GREAT KNOWLEDGE. IN ADDITION, THE ACTION CONTRIBUTED TO THE GROWTH OF EACH ACADEMIC, BEING A GREAT OPPORTUNITY TO COMBINE THEORETICAL KNOWLEDGE WITH PRACTICE, ON A CRUCIAL SUBJECT IN DENTISTRY: PREVENTION AND HEALTH PROMOTION.